2018
DOI: 10.3390/rs10050763
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Comparison of Remote Sensing Leaf Area Index Estimates over Rice-Cultivated Areas: From Sentinel-2 and Landsat-7/8 to MODIS, GEOV1 and EUMETSAT Polar System

Abstract: Leaf area index (LAI) is a key biophysical variable fundamental in natural vegetationand agricultural land monitoring and modelling studies. This paper is aimed at comparing, validating and discussing different LAI satellite products from operational services and customized solution based on innovative Earth Observation (EO) data such as Landsat-7/8 and Sentinel-2A. The comparison was performed to assess overall quality of LAI estimates for rice, as a fundamental input of different scale (regional to local) op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…Indeed, the comparison at a spatial resolution of 3 km shows similar product accuracy (just slightly better) to that at a resolution of 300 m. The accuracy of Collection 300 m V1 is similar to that of the other reference satellite 1 km products for LAI and improved for fAPAR. All the satellite products show large overestimations for the Albufera rice crop site during the early and growing periods of development (June-July), and this result was previously observed for LAI products by Campos-Taberner et al [68] and by Fang et al [69] for rice crops in China. Satellite retrieval algorithms misinterpret the decreased reflectance due to strong water absorption as a denser canopy (i.e., increasing artificially LAI, fAPAR and fCOVER values).…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, the comparison at a spatial resolution of 3 km shows similar product accuracy (just slightly better) to that at a resolution of 300 m. The accuracy of Collection 300 m V1 is similar to that of the other reference satellite 1 km products for LAI and improved for fAPAR. All the satellite products show large overestimations for the Albufera rice crop site during the early and growing periods of development (June-July), and this result was previously observed for LAI products by Campos-Taberner et al [68] and by Fang et al [69] for rice crops in China. Satellite retrieval algorithms misinterpret the decreased reflectance due to strong water absorption as a denser canopy (i.e., increasing artificially LAI, fAPAR and fCOVER values).…”
Section: Discussionsupporting
confidence: 76%
“…Similar underestimation behaviour was found by other studies when comparing MODIS LAI products and LAI retrievals from RTM inversion [59,63]. Yan et al [59] found RMSE = 0.66 m 2 /m 2 and RMSE = 0.77 m 2 /m 2 when comparing MODIS C6 LAI estimates with ground LAI actual and LAI e f f measurements respectively, as well as larger uncertainties in high LAI values.…”
Section: Discussionsupporting
confidence: 68%
“…According to previous studies, the uncertainty of Sentinel-2 LAI estimates was generally 0.54-1.16 m 2 /m 2 for crops [36,37,39,46,47,[50][51][52] and 1.55 m 2 /m 2 for forest [49]. In terms of Sentinel-2 FAPAR estimates, the uncertainty was 0.11 for crops [39] and 0.16-0.24 for forests [38].…”
Section: Limitations and Future Prospectsmentioning
confidence: 82%